2011
DOI: 10.1007/s12519-011-0328-y
|View full text |Cite
|
Sign up to set email alerts
|

Twelve-year prevalence of common neonatal congenital malformations in Zhejiang Province, China

Abstract: The incidences of CHD, intestinal atresia/stenosis, kidney malformations, hypospadias, OFC, and accessory auricle anomaly have increased in the last 12 years, but the incidences of anorectal malformations, polydactyly and syndactyly remain stable. The incidence of hydrocephalus shows a downward trend.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
15
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 28 publications
4
15
0
Order By: Relevance
“…Our polydactyly prevalence of 6.45/10,000 live births was comparable to other European prevalence rates of 6.79/10,000 for Belgium, 6.80/ 10,000 for Paris, and 6.6/10,000 for Portugal respectively [10]. The prevalence of this birth defect is much higher in China (22.4/10, 000) [34] and in Alberta, Canada (18.84/10,000) [9]. Prevalence of polydactyly was reported to be lower in Barcelona, Spain (3.06/10,000) [10] and in Lombardy, Italy (5.82/10,000) [27].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Our polydactyly prevalence of 6.45/10,000 live births was comparable to other European prevalence rates of 6.79/10,000 for Belgium, 6.80/ 10,000 for Paris, and 6.6/10,000 for Portugal respectively [10]. The prevalence of this birth defect is much higher in China (22.4/10, 000) [34] and in Alberta, Canada (18.84/10,000) [9]. Prevalence of polydactyly was reported to be lower in Barcelona, Spain (3.06/10,000) [10] and in Lombardy, Italy (5.82/10,000) [27].…”
Section: Discussionsupporting
confidence: 80%
“…It is a defect that is easily detectable after birth and is an isolated finding in 85% - 88% of cases [34]. Our polydactyly prevalence of 6.45/10,000 live births was comparable to other European prevalence rates of 6.79/10,000 for Belgium, 6.80/ 10,000 for Paris, and 6.6/10,000 for Portugal respectively [10].…”
Section: Discussionsupporting
confidence: 76%
“…1,3 Syndactyly is one of the most commonly observed congenital malformations, affecting an estimated 1 in 2000 to 2500 live births (0.04%-0.05%), with regional occurrence rates ranging between 0.06% to 0.12%. [3][4][5][6] The genetic phenomenon of mosaicism, whereby 2 genetically distinct populations of cells coexist within an individual' s somatic cells or gametes, has been observed in TS1 individuals/ families on at least 3 separate occasions.…”
mentioning
confidence: 99%
“…Smaller studies regarding certain areas such as Italy also showed similar rates (Calzolari et al, ). However, it must be kept in mind that the incidences of certain congenital malformations change by time due to health policies or environmental exposures (Hoffmann, ; Sun, Xu, Liang, Li, & Tang, ). There are also several studies showing that the incidence of congenital abnormalities tend to be decreasing in last decade (Yu et al, ).…”
Section: Discussionmentioning
confidence: 99%